A Nonlinear Relationship Between Serum 25-Hydroxyvitamin D and Urine Albumin to Creatinine Ratio in Type 2 Diabetes: A Cross-Sectional Study in China - Liang Q (Dove Medical Press, 2021)
Qian Liang,1– 3,* Haofei Hu,4,* Han Wu,1– 3 Xuan Chen,1– 3 Wei Wang,1– 3 Ying Le,1– 3 Shufen Yang,1– 3 Lijing Jia1– 3 1Department of Endocrinology, Shenzhen People’s Hospital, Shenzhen, 518020, Guangdong Province, People’s Republic of China; 2Department of Endocrinology, The First Affiliated Hospital of Southern University of Science and Technology, Shenzhen, 518020, Guangdong Province, People’s Republic of China; 3Department of Endocrinology, The Second Affiliated Hospital of Jinan University, Shenzhen, 518020, Guangdong Province, People’s Republic of China; 4Department of Nephrology, Shenzhen Second People’s Hospital, Shenzhen, 518000, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lijing JiaDepartment of Endocrinology, Shenzhen People’s Hospital, 1017 Dongmen North Road, Luohu District, Shenzhen, Guangdong Province, People’s Republic of ChinaEmail srmyynfmk@126.comBackground: Diabetic kidney disease often presents as increased urine albumin to creatinine ratio (UACR). 25-hydroxyvitamin D (25(OH)D) is considered as the best indicator of vitamin D status. Previous studies have shown that 25(OH)D is related to the UACR. However, evidence concerning the connection between 25(OH)D and UACR is still limited in the Chinese population.Materials and Methods: A total of 549 participants with type 2 diabetes were enrolled in the study from Shenzhen People’s Hospital, China. The participants were grouped by the tertiles of 25(OH)D level. The association between 25(OH)D and UACR was examined by multiple linear regression. A generalized additive model (GAM) was used to verify a non-linear relationship. We conducted a subgroup analysis to evaluate the robustness of the results.Results: After adjusting for relevant variables, 25(OH)D was negatively correlated with UACR (β = − 8.7, 95% CI (− 12.0, − 5.4)). A non-linear relationship was discovered between 25(OH)D and UACR, and the 25(OH)D threshold was 67. The effect sizes and confidence intervals on the left and right sides of the inflection point were − 13.9 (− 18.2, − 9.6) and 8.9 (− 1.1, 18.9), respectively. Subgroup analysis showed a stronger correlation could be detected in males. The same trend also could be found in patients older than 70 years old, those with using ACEI/ARB, with history of hypertension, with SBP ≥ 140 mmHg and eGFR < 60 mL/min/1.73m2.Conclusion: The relationship between 25(OH)D and UACR is non-linear. 25(OH)D was negatively related to UACR when 25(OH)D is less than 67 nmol/L.Keywords: 25-hydroxyvitamin D, urine albumin to creatinine ratio, nonlinearity